Papua New Guinea : Request for a Staff-Monitored Program; and Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
Papua New Guinea (PNG) is a fragile state, vulnerable to recurrent shocks. A third wave of the COVID-19 pandemic is straining the healthcare system. Widespread vaccine hesitancy has contributed to very low uptake of the vaccines with about only 2 percent of the population fully vaccinated. Real GDP is estimated to rebound modestly to grow by 1.7 percent in 2021 after the downturn in 2020. Elections are due to take place in June 2022, and the formal campaign period will commence by end-April.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Colombia